Solute Carrier 45A1: A New Cerebral Glucose Transporter Brain Disorder with Focal Refractory Epilepsy Responsive to Ketogenic Diet and Acetazolamide - Semal, Benoit; Neuens, Sebastian; Vilain, Catheline; De Laet, Corinne; Leurquin-Sterk, Gil; Sculier, Claudine; Baijot, Simon; Aeby, Alec (Neuropediatrics, 2025)
Solute carrier family 45 member A1 (SLC45A1) is a glucose brain transporter predominantly expressed in the developing and adult brain, including the cortex and cerebellum. Pathogenic variants in SLC45A1 have been described in four patients from two unrelated families with dysmorphic features, intellectual disability, and focal epilepsy. We describe the fifth SLC45A1 patient, presenting with focal refractory epilepsy responsive to ketogenic diet (KD) and acetazolamide.A 3-year-old boy presented with developmental delay and unexpected nighttime arousals followed by sudden right arm extension suggestive of epilepsy. Long-term video electroencephalogram and semiology were evocative of a left-frontal focus. Brain magnetic resonance imaging (MRI) was normal. Clinical exome, metabolic evaluation, and lumbar puncture were non-contributive. The patient was treated unsuccessfully with carbamazepine, valproate, levetiracetam, lamotrigine, topiramate, lacosamide, and clobazam. Presurgical evaluation was planned because of refractory epilepsy. Meanwhile, a KD was introduced, and the child became seizure-free with cognitive improvement. After 2 years, the KD was stopped, and seizures relapsed. Acetazolamide was introduced with seizure freedom for 10 months. Exome analysis revealed compound heterozygous variants p.Pro560Leu and p.Arg57Cys in the SLC45A1 gene.This case illustrates that KD and acetazolamide might be effective in SLC45A1-related epilepsy and underscores the importance of genetic testing in the presurgical evaluation of epilepsy.
Keywords: epilepsy; acetazolamide; ketogenic diet; SLC45A1